CRYSTAL-CHEMICAL REASONS FOR THE IMMISCIBILITY OF PERICLASE AND WüSTITE UNDER LITHOSPHERIC P, T CONDITION - Boiocchi M.; Caucia F.; Merli M.; Prella D.; Ungaretti L. (My University, 2001)
We have analyzed the implications of [Mg](VI)double right arrow [Fe2+](VI) isomorphous substitution in the periclase structure (B1) which forms, under lithospheric P, T conditions, only very limited solid solutions with wustite. The crystallographic study (by single crystal X-ray structure refinements and microprobe analysis) supports the key role of the cation-cation repulsive interactions in the crystal-chemical behaviour of these closely-packed phases. The anomalously large octahedral bond lengths in periclase (Mg-O=2.106 Angstrom) and in wustite (Fe-O=2.167 Angstrom) are the result of otherwise too short M-M distances (=1.414 . M-O). In particular, the wustite instability below 570 degreesC and the problematic existence of a stoichiometric iron end-member indicate that the M-M separation in the "ideal" wustite, although largely increased by the anomalously large Fe-O bond length, is still too short to support the B1 structure. Any periclase-wustite solid solution with a wustite component higher than 8.3 % necessarily entails the presence of couples of adjacent [Fe2+](VI) cations with separations shorter than that of "ideal" wustite; this makes the solid solutions in this system even less stable than the pure wustite. One easy way to reduce the electrostatic [Fe2+](VI)-[Fe2+](VI) repulsion, and therefore the instability of iron-bearing periclase, is the iron oxidation with the formation of a more stable spinel phase (magnesioferrite), as it has been demonstrated by heat treatment and structure refinement of several natural ferropericlase crystals with 2-5 % of wustite component. Magnesioferrite has a unit-cell edge of 8.39 Angstrom which is almost twice the unit-cell of periclase (2 . 4.21 = 8.42 Angstrom) and this allows the spinel to grow with the same orientation of periclase, being the oxygen arrangement of the two structures virtually identical. Under very high pressure (greater than or equal to 90 GPa) the electrostatic [Fe2+](VI)-[Fe2+](VI) repulsion of FeO can be greatly reduced by a phase transition from B1 to B8 (NiAs) structure. In the B8 phase the Fe-Fe separation becomes 2.57 Angstrom; this short value corresponds to a change in the electronic properties of iron which can now form metallic bonds, in contrast to MgO (B1) phase which is supposed to maintain its stability up to at least 230 GPa.